SUBEPENDYMAL GIANT-CELL ASTROCYTOMAS IN TUBEROUS SCLEROSIS - (:unkn) unknown (TURKISH J PEDIATRICS, 1993)
Two cases of tuberous sclerosis with subependymal giant cell astrocytoma are presented. This rare autosomal dominant disorder was also detected in family members of the patients who had never had any symptoms of cerebral involvement. Both patients underwent surgery because of signs of increased intracranial pressure.
Keywords: TUBEROUS SCLEROSIS; SUBEPENDYMAL GIANT CELL ASTROCYTOMA